O/W microemulsion droplets diffuse through hydrogel network to achieve enhanced transdermal drug delivery. (1st January 2021) - Shen, Lina; Hou, Xiaolin; Wang, Zhi; Guo, Teng; He, Zehui; Ruan, Shuyao; Liu, Zhenda; Ruan, Hang; Zhang, Yongtai; Feng, Nianping
Abstract: To overcome the poor water solubility of total flavones of Arisaematis rhizoma, microemulsions (MEs) can be used as a carrier for transdermal administration to promote their solubilization and skin permeability. Here, we investigated the physical compatibility of MEs in hydrogels and their skin permeation-enhancing effects. Transparency of microemulsion-based hydrogels (MBGs) was analyzed to evaluate ME compatibility with different hydrogel matrices. Transmission electron microscopy (TEM) and Fourier transform infrared (FTIR) spectroscopy were used to explore the microstructures of MBGs and ME–hydrogel combinations. Uniform and transparent MBG was obtained by adding 1% sodium hyaluronate (SH) to the optimized ME. MBG prepared with SH as a matrix expressed pseudoplastic-fluid and shear-thinning characteristics, making it easy to apply in clinical settings. No new FTIR peak occurred in the MBG compared with ME and hydrogel matrix, indicating a physical combination of ME and the polymer network gel. Nanoscale droplets of ME migrated in the gel network, and the migration capacity and in vitro transdermal permeation flux negatively correlated with SH concentration in the gel system. In conclusion, in MBGs, ME can keep nanoscale droplets migrating in the hydrogel network, thereby enhancing transdermal drug delivery.